SOCIALIZATION AND EDUCATION OF THE 3R PRINCIPLES (REDUCE, REUSE, RECYCLE) IN WASTE REDUCTION AT THE 3R TPS IN BANYUMUDAL VILLAGE, MOGA DISTRICT, PEMALANG REGENCY - Widodo, Agus Setio; Harto, Unggul Sugi (Universitas Pancasakti Tegal, 2025)
The extremely high waste production of 110.77 cubic meters per day (dlh.pemalangkab.go.id, 2024) in Moga District makes waste management a crucial issue. In addition to the overcapacity of the final processing site (TPA), low public understanding of waste sorting and processing is a major obstacle to waste management in Moga District, Pemalang Regency. Moga District was chosen as the location for this community service program because it is one of the largest waste producers in the southern region of Pemalang Regency. The 3R principle socialization activity, held in conjunction with the Community Service Program (KKN) of the BDS (Bina Desa Sakti) program at Pancasakti University, Tegal, aimed to educate the community and administrators of the 3R waste processing site (TPS) in Banyumudal Village, Moga District, about the importance of optimizing the 3R TPS in waste management.